Micromechanical modeling and evaluation of CNTs reinforced magnesium matrix composites based on stress softening modified constitutive model - Mingjie Shen; Baojian Han; Tao Ying; Jingya Wang; Liping Zhou; Xiangzhen Xue; Yang Gao; Zongyang Yang (Journal of Magnesium and Alloys)
Heterogeneous composites have strong anisotropy and are prone to dynamic recrystallization during hot compression, making the mechanical response highly nonlinear. Therefore, it is a very challenging task to intellectually judge the thermal deformation characteristics of magnesium matrix composites (MgMCs). In view of this, this paper introduces a method to accurately solve the thermoplastic deformation of composites. Firstly, a hot compression constitutive model of magnesium matrix composites based on stress softening correction was established. Secondly, the complex quasi-realistic micromechanics modeling of heterogeneous magnesium matrix composites was conducted. By introducing the recrystallization softening factor and strain parameter into the constitutive equation, the accurate prediction of the global rheological response of the composites was realized, and the accuracy of the new constitutive model was proved. Finally, the thermal processing map of magnesium matrix composites was established, and the suitable processing range was chosen. This paper has certain guiding values for the prediction of the thermodynamic response and thermal processing of magnesium matrix composites.